Implementation of 4D/BIM in the Iraqi construction industry. (2017) - Hamada, Hussein Mahmood; Haron, Ahmad Tarmizi; Zahrizan, Zahrizan Zakaria; Humada, Ali M.
Building information modelling (BIM) is a new technique, which has been innovated from the traditional method to a modern form. BIM should be classified as a modern technique, since it is dealing with digital data. 3D BIM with its time schedule results on 4D/BIM is represented by softwares, such as Naviswork and Syncro, which has an advantage to solve most of the project issues such as clash detection among projects components, visualisation to projects tasks, and other benefits. The aim of this current study is to find out the benefits and challenges of 4D/BIM implementation in the construction projects. The data collection method in this research is done by conducting semi-structured interviews (SSIs) with the senior civil engineer in Al-Najaf hospital project in Iraq, in addition to that there is the extensive literature review about the benefits, challenges and obstacles in the implementation of 4D/BIM. Analysis of the results was conducted by adopting content analysis method (CAM). The results proved that the construction industry in Iraq needs to further support from the government by increasing awareness and financial support for construction companies.